Epidemiology of preoperative hyperglycaemia among patients undergoing surgery at a tertiary health care facility of Eastern India - Banerjee, Souvik; Kumar, Rakesh; Basu, Debasis (International Journal Of Community Medicine And Public Health, 2019)
Background: With about 425 million patients globally and 72.9 million patients in India, diabetes mellitus (DM) is one of the global health emergency of 21st century. Perioperative hyperglycaemia is reported in 20-40% of patients undergoing general surgery. A substantial body of literature demonstrates a clear association between perioperative hyperglycaemia and adverse clinical outcomes. This study aims to find out the frequency of preoperative hyperglycaemia and factors influencing it among patients undergoing surgery at a tertiary health care hospital of Eastern India. Methods: This Institution based, cross-sectional, observational study was conducted among study subjects who were operated at IQ City Medical College and Multispecialty Hospital, Durgapur, India during January-February 2019. Relevant medical records were reviewed to collect data regarding clinic-social data. Estimation of fasting plasma glucose (FPG) has been done as per World Health Organization (WHO) guidelines. Hyperglycaemia was defined and classified as per American Diabetes Association (ADA). Anthropometric measurements were taken as per standard WHO protocols. Results: A total 158 study subjects participated in study. The mean age and mean FPG of the study subjects was 42.63±12.95 years and 103.3±17.37 mg/dl respectively. As per the ADA criteria, 58.9% had normal FPG, 24.0% had impaired fasting glucose (IFG) and 17.1% had diabetes. Out of total 27 T2DM patients, 22 (13.9%) were known cases of T2DM and 5 (3.2%) were undiagnosed. The frequency of preoperative hyperglycaemia i.e. sums of IFG and diabetes was found to be 41.1%. Increasing age, male gender and overweight and obesity significantly influenced the occurrence of preoperative hyperglycaemia. Conclusions: The prevalence of preoperative hyperglycaemia among patients undergoing surgery is higher than the prevalence of hyperglycaemia among non surgical patients. Routine HbA1C should be done in all surgical patients to differentiate between chronic undiagnosed hyperglycaemia and stress hyperglycaemia.